การศึกษาการจัดการพยาบาลในภาวะภัยพิบัติสำหรับผู้สูงอายุ - โชคทวีพาณิชย์ นิตยา; วิวัฒน์วานิช สุวิณี (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อศึกษาการจัดการพยาบาลในภาวะภัยพิบัติสำหรับผู้สูงอายุโดยใช้เทคนิคเดลฟาย ผู้ให้ข้อมูลเป็นผู้เชี่ยวชาญที่มีประสบการณ์ทำงานในภาวะภัยพิบัติสำหรับผู้สูงอายุ จำนวน 20 คน ประกอบด้วย ผู้บริหารการพยาบาล 4 คน ผู้ปฏิบัติการพยาบาล 5 คน อาจารย์พยาบาล 4 คน แพทย์ผู้เชี่ยวชาญ 4 คน และผู้มีประสบการณ์การจัดการภาวะภัยพิบัติสำหรับผู้สูงอายุในชุมชน 3 คน เครื่องมือที่ใช้ในการวิจัยมี 3 ชุด คือ ชุดที่ 1 แบบสอบถามและแบบสัมภาษณ์กึ่งโครงสร้างชนิดปลายเปิด ที่ผู้วิจัยสร้างขึ้นจากการทบทวนวรรณกรรม ชุดที่ 2 ความคิดเห็นที่ได้จากผู้เชี่ยวชาญ สร้างเป็นแบบสอบถามแบบมาตราส่วนประมาณค่า 5 ระดับ และชุดที่ 3 คำตอบที่ได้ในรอบที่ 2 มาคำนวณทางสถิติ และส่งกลับให้ผู้เชี่ยวชาญได้ตอบยืนยันความคิดเห็น ระยะเวลาที่ใช้ในการเก็บข้อมูล 3 รอบ จำนวน 161 วัน วิเคราะห์ข้อมูลโดยการวิเคราะห์เนื้อหา สถิติค่ามัธยฐาน (Median: Md) และค่าพิสัยระหว่างควอไทล์ (Inter-quartile Range: IR) ผลการวิจัยพบว่า การศึกษาการจัดการพยาบาลในภาวะภัยพิบัติสำหรับผู้สูงอายุประกอบด้วย การจัดการพยาบาล 4 ระยะ 13 ด้าน จำนวน 47 ข้อรายการ ผู้เชี่ยวชาญให้ความสำคัญในระดับมากที่สุด 38 ข้อรายการ และระดับมาก 9 ข้อรายการ การจัดการพยาบาลในภาวะภัยพิบัติสำหรับผู้สูงอายุ จึงสามารถแบ่งได้ดังนี้ 1. ระยะป้องกันและลดผลกระทบของภัยพิบัติ ประกอบด้วย 3 ด้าน จำนวน 13 ข้อรายการ 2. ระยะการเตรียมพร้อมรับภัยพิบัติ ประกอบด้วย 3 ด้าน จำนวน 11 ข้อรายการ 3. ระยะตอบสนองต่อภัยพิบัติ ประกอบด้วย 5 ด้าน จำนวน 15 ข้อรายการ 4. ระยะฟื้นฟูหลังเกิดภัยพิบัติ ประกอบด้วย 2 ด้าน จำนวน 8 ข้อรายการ A Study of Disaster Nursing Management for the Elderly. Abstract The purpose of this research was to study disaster nursing management for the elderly. A Delphi technique was applied. Twenty experts including 4 nursing administrators, 5 staff nurses, 4 nurse instructors, 4 medical physicians and 3 stakeholders were get experienced in disaster nursing management. The instruments were developed by the researcher, including (1) a semi-structure interview with open ended questionnaire for asking the experts to describe the disaster nursing management for the elderly. (2) and (3) a questionnaire with 5-scale rating developed from the interview contents to ask a prior panel of experts for confirming the previous opinion. The data was collected 3 times within 161 days. The content analysis was used. The statistics were median (Md) and inter-quartile range (IR). The results revealed that the study disaster nursing management for the elderly were classified into 4 phase 47 items. The experts absolutely accorded that 38 items were evaluated as the most essential and the other 9 items essential. These 47 items can be classified into 13 domains as follows: 1. Prevention and Mitigation Phase: included 3 domains, composed of 13 items. 2. Preparedness Phase: included 3 domains, composed of 11 items. 3. Response Phase: included 5 domains, composed of 15 items. 4. Recovery Phase: included 2 domains, composed of 8 items.